Visual landscapes preference for farmers in southern Brazil - Kelia Leite, Siderlania; Anélia Renk, Arlene; Kissmann, Camila; Vendruscolo, Giovana (Sociedade & Natureza, 2020)
Landscape preference varies according to the cultural and social experiences of the individual. People preferred landscapes are related to natural environments, with the presence of vegetation and water. Age and gender are variables that can influence landscape preference, especially the feeling of security related to age and aesthetics with gender. This study aimed to analyze the visual preference for the landscape by farmers and to assess whether age and gender are variables related to this preference. Farmers from the Western Region of Santa Catarina, southern Brazil, were interviewed, using semi-structured interviews to collect social and cultural data, and the Q method, through photographs, to identify landscape preferences. Discourses, gradient of landscape preference and influence of age and gender on this preference in the results were identified using multivariate analyzes and statistical tests. Three discourses of landscape preference were identified: natural landscape for appreciation and recreation; rural landscape as familiarity; and cultural landscape. The farmers' preference followed the gradient natural > rural > urban > degraded landscapes. Natural elements with native vegetation and water were preferred in the landscape while environmental degradation, forestry and urban environments without natural green elements were rejected. The lower the age the higher the preference for natural landscapes and the higher the age the higher the preference for urban landscapes. In relation to gender, differences were observed only regarding the landscape with forestry. Consider the perceptions of people in urban and rural landscape management is important for the population to identify with the place they reside. In this perspective, this study demonstrated that farmers do not identify with degraded landscapes and with urban landscapes without the presence of trees.